Jenis dan istilah hadis dalam Jami` Al-Turmudhi: satu kajian - Ahamad Asmadi bin Sakat (Penerbit Universiti Kebangsaan Malaysia, 2007)
This study is to present the categories and terminologies of the Prophetic tradition used in Jami' by al-Turmudhi and the methodology that he applied to differentiate those categories and terminologies. This study clearly proves his authority and scholarship in the Prophetic tradition studies as well as his bravery in introducing the new terminologies, unknown among the earlier Muslim traditionists. Hence al-Turmudhi is a learned and erudite Muslim traditionist due to his contributions to the Prophetic tradition studies. This study is an introduction to Jami' by al- Turmudhi